Analisis Penanggulangan Kemiskinan Melalui Implementasi Program Dana Bergulir Badan Amil Zakat Kota Bandung - Hani Widyani (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
This article analyzes and evaluates the implementation of poverty alleviation program run by Zakat Collector (BAZ) in Bandung Mucipality. Just like other zakat collectors in Indonesia, BAZ of Bandung Mucipality has various development programs for poverty alleviation, including what is to be called revolving fund project. The aim of revolving fund project is to support the poor to run micro business. Based on fieldwork in Bandung, this article exmanines the problems and difficulties faced by the zakat collector in running development-oriented project and how poverty alleviation are still hard to reach. In evaluating the implementation of poverty alleviation program in Bandung, this article highlights five aspects, including communication, human resource, disposition, bureaucratic structures, and social-economic condition. This article concludes that one of the problems faced by zakat collector is ineffectiveness of communitation between zakat collectors in District and Sub-District levels, as well as lack of capacity among the staff in sub-district level in providing technical assistance for zakat beneficiaries. Keywords: zakat, qardhul hasan, poverty avaliation, revolving fund